Electronic Assessment of Momentum and Impulse Materials is Practical: In Assessing Students' Critical Thinking Skills? - Oktaviawati, Diah ayu; Mufit, Fatni (Department of Physics Universitas Negeri Padang, 2025)
The problem of low critical thinking skills in physics learning and the unavailability of assessments that assess students' critical thinking skills, especially in momentum and impulse material. The use of technology that has not been maximized in learning. One solution to some of these problems is to develop electronic assessments to assess students' critical thinking skills on momentum and impulse materials. This study aims to analyze the practicality of electronic assessment products to assess critical thinking skills on momentum and impulse materials. This research uses the Plomp model. This research reports the development stage in the Plomp model, namely at the one to one and small group practicality test stages. This research instrument is in the form of a practicality questionnaire which is analyzed by percentage technique. The results of the practicality test of the electronic assessment product obtained an average percentage of 89.48 with very practical criteria. Electronic assessment to assess students' critical thinking skills on momentum and impulse material is declared practical for students from the aspects of convenience, attractiveness, efficiency and benefits so that it is feasible to use.